2009
DOI: 10.1088/0031-9155/54/12/005
|View full text |Cite
|
Sign up to set email alerts
|

Determining charge collection efficiency in parallel-plate liquid ionization chambers

Abstract: An accurate computation of the collection efficiency due to recombination has a capital importance in order to perform high-precision dose measurements with ionization chambers. The two-voltage method, developed to compute charge collection efficiency in gas chambers, cannot be directly applied to liquid-filled ionization chambers (LICs) due to the ionized charge strong dependence on the collection electric field, which is caused by initial recombination. It is shown that in order to apply the two-voltage meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 21 publications
0
30
0
Order By: Relevance
“…, cannot be applied directly to ionized liquids without a robust theoretical description of initial recombination. An experimental solution to this problem for continuous beams has been found by employing a two‐dose‐rate method, based on the general collection efficiency according to Greening, to disassociate initial and general recombination in LICs . This method is straightforward, involving charge measurements (Q ) with a reference detector with a signal proportional to dose, here charge readings with an air‐filled ionization chamber (REF) corrected according to the two‐voltage method, and a LIC at two different dose rates (d1 and d2) to experimentally determine the parameter italicξ2d1, as described in Eq.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…, cannot be applied directly to ionized liquids without a robust theoretical description of initial recombination. An experimental solution to this problem for continuous beams has been found by employing a two‐dose‐rate method, based on the general collection efficiency according to Greening, to disassociate initial and general recombination in LICs . This method is straightforward, involving charge measurements (Q ) with a reference detector with a signal proportional to dose, here charge readings with an air‐filled ionization chamber (REF) corrected according to the two‐voltage method, and a LIC at two different dose rates (d1 and d2) to experimentally determine the parameter italicξ2d1, as described in Eq.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, loss of measurement signal due to both initial and general recombination can be severe in LICs, limiting the usability of these instruments for both quality assurance and radiation dosimetry. In recent years, two methods have been proposed for the purpose of general recombination correction for LICs, the three‐voltage method and the two‐dose‐rate method . A comparative investigation of these methods has been done, where it could be concluded that the two‐dose‐rate method is more robust than the three‐voltage method .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…General collection efficiencies, f, in LICs irradiated with pulsed radiation beams are well described in the near saturation range f 4 0:9 by the Boag equation [14][15][16]8]:…”
Section: General Recombinationmentioning
confidence: 99%
“…Much effort has therefore been given in finding experimental 75 methods that accurately correct for general recombination losses. [10][11][12][13][14] …”
mentioning
confidence: 99%